Analysis of Information System Quality and Customer Satisfaction Using the PIECES Framework at Warkop Abas Jakarta - Ridho Arif Hidayat; Sri Lestari; Mesra Betty Yel (PT. Lentera Ilmu Publisher, 2026)
Advancements in information technology have encouraged business operators, including micro, small, and medium-sized enterprises (MSMEs), to leverage information systems to enhance service quality and customer satisfaction. Warkop Abas, a culinary business in East Jakarta, utilizes an information system to support its operations; however, the quality of this system has never been systematically evaluated. This study aims to analyze the information system's quality based on the six PIECES dimensions (Performance, Information, Economics, Control, Efficiency, and Service) and their impact on customer satisfaction, both simultaneously and partially, while identifying the most dominant dimension. A quantitative approach was employed, utilizing a survey of 1,000 Warkop Abas customers; data were analyzed using IBM SPSS Statistics through validity, reliability, and multiple linear regression tests. The results indicate that all statement items were valid and all variables were reliable (Cronbach's Alpha > 0.70). Simultaneously, the six PIECES dimensions significantly influenced customer satisfaction (F = 1069.263; p = 0.000), with an R-square value of 0.866. Individually, the Performance, Information, Economics, Control, and Efficiency dimensions showed a significant impact, whereas the Service dimension did not. The Efficiency dimension emerged as the most dominant factor (Beta = 0.272) influencing customer satisfaction at Warkop Abas.